2016
DOI: 10.21315/kajh2016.23.s2.3
|View full text |Cite
|
Sign up to set email alerts
|

An Ideological Construction of the Indigenous Community: The Orang Asli as Portrayed in The Star Newspaper

Abstract: Abstract. Powerful western nations, especially those which control global news media, tend to portray less powerful nations through a Western-centric lens or perspective in globalised space. As such, less powerful nations are depicted as weak and powerless victims, reinforcing in the process prevailing power structures or unequal relations between powerful nations and less powerful ones. Minority groups are also not spared as they are, more often than not, depicted in a similar negative way. Interestingly, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…These features use to marginalize the figures of house representative of Indonesia. The marginalization of the media also found in Jamal & Manan (2016) research which analyzed the thematic structure and lexical, syntactic and rhetorical structures. Their study explained that orang asli or indigenous community are portrayed negatively with the stereotypical image of being traditional, primitive and responsible for their own pitiful life by Star Newspaper.…”
Section: Introductionmentioning
confidence: 84%
“…These features use to marginalize the figures of house representative of Indonesia. The marginalization of the media also found in Jamal & Manan (2016) research which analyzed the thematic structure and lexical, syntactic and rhetorical structures. Their study explained that orang asli or indigenous community are portrayed negatively with the stereotypical image of being traditional, primitive and responsible for their own pitiful life by Star Newspaper.…”
Section: Introductionmentioning
confidence: 84%
“…Much of the literature has revolved around the historical background, sociopolitical, socioeconomic, and more recently the contemporary issues surrounding the Orang Asli such as social issues concerning their land rights, health, and education. Thus far, studies which have examined the representation of the Orang Asli in the media have revealed that the community does not enjoy a fair and balanced portrayal by the mainstream media and is consistently represented in a stereotypical and demeaning manner [4,16,17,18,19,36,37]. Despite the findings, both journalists and JAKOA themselves have strongly refuted the claim that the Orang Asli are represented in such a manner [36].…”
Section: Past Studiesmentioning
confidence: 99%
“…Several existing studies have consistently revealed the discursive practices of the media in constructing the indigenous communities as stereotypical and troublesome [12], primitive [13], emotional and aggressive [14], and paternalistically [15]. Likewise, in the Malaysian context, the Orang Asli as the indigenous peoples of the country have received similar treatment by the local mainstream media which portrays them in a prejudiced and inferior manner [4,16,17,18,19]. Hence, these past literature reveals that the media tends to position and emphasise the negative attributes and qualities of these communities as the significant "Other" or outcasts of society.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patterns of bias or misrepresentation are found in studies conducted in Malaysia where negativity appears to be the pulling factor of newsworthiness for stories about the Orang Asli (Mustafa, 1994), and their portrayal are depicted in a stereotypical way (Jamal & Manan, 2016). Often they are portrayed as "victim or beneficiary" (Alagappar, 2010, p. 12).…”
Section: Introductionmentioning
confidence: 99%